Synergistic effect of well-defined dual sites boosting the oxygen reduction reaction. Issue 12 (23rd November 2018) - Wang, Jing; Liu, Wei; Luo, Gan; Li, Zhijun; Zhao, Chao; Zhang, Haoran; Zhu, Mengzhao; Xu, Qian; Wang, Xiaoqian; Zhao, Changming; Qu, Yunteng; Yang, Zhengkun; et al.
Abstract : Herein, we construct a novel electrocatalyst with Fe–Co dual sites embedded in N-doped carbon nanotubes ((Fe, Co)/CNT), which exhibits inimitable advantages towards the oxygen reduction reaction. Abstract : Herein, we construct a novel electrocatalyst with Fe–Co dual sites embedded in N-doped carbon nanotubes ((Fe, Co)/CNT), which exhibits inimitable advantages towards the oxygen reduction reaction. The electrocatalyst shows state-of-the-art ORR performance with an admirable onset potential ( E onset, 1.15 V vs. 1.05 V) and half-wave potential ( E 1/2, 0.954 V vs. 0.842 V), outperforming those of the commercial Pt/C. The ORR test reveals that the performance of the (Fe, Co)/CNT is superior to most of the reported non-precious catalysts in alkaline electrolytes. Furthermore, when employed as a cathode catalyst in a Zn–air battery, the (Fe, Co)/CNT exhibits high voltages of 1.31 V and 1.23 V at discharge current densities of 20 mA cm −2 and 50 mA cm −2, respectively. In addition, the power density and the specific energy density reach 260 mW cm −2 and 870 W h kgZn −1 . We discover that the Fe–Co dual sites embedded in N-doped porous carbon are beneficial for the activation of oxygen by weakening the OO bonds.